EFEKTIVITAS MODEL CUPS BERBANTUAN E-LKPD DALAM MENINGKATKAN PENALARAN DAN KOMUNIKASI MATEMATIS SISWA - Rahmadani, Noviana Dwi; Anggoro, Bambang Sri; Dewi, Novian Riskiana (De Fermat : Jurnal Pendidikan Matematika, 2026)
Mathematical reasoning and communication skills are essential for building conceptual understanding, yet conventional learning practices often fail to optimize them. This study aims to examine the effectiveness of the Conceptual Understanding Procedures (CUPs) model assisted by E-LKPD (Electronic Student Worksheet) in enhancing both abilities. Using a quantitative approach with a quasi-experimental design, the study was conducted on three eighth-grade classes at SMPN 21 Bandar Lampung selected through cluster random sampling: experimental class 1 (CUPs assisted by E-LKPD), experimental class 2 (CUPs without E-LKPD), and control class (discovery learning). Data were collected through tests of mathematical reasoning and communication, then analyzed using MANOVA at a significance level of 5%. The results showed that the CUPs model assisted by E-LKPD provided the most significant improvement compared to the other two classes. Based on MANOVA, there was a significant simultaneous effect on mathematical reasoning and communication abilities, with Wilks' Lambda = 0.014, F = 2737.056b, p = 0.000 (p < 0.05), and partial eta squared (η²) = 0.986, indicating a large effect. This success is supported by the ease with which the E-LKPD presents interactive questions that structure conceptual understanding procedures, although technical constraints such as network instability and some students' relaxed attitudes were observed. These findings confirm the effectiveness of the CUPs model assisted by E-LKPD as an innovative learning alternative that addresses the challenge of developing higher-order thinking skills in the digital era